(untitled) (Gestão & Regionalidade, 2024)
The ongoing debate over development strategies highlights the importance of infrastructure to boost economic and social growth, but several studies have pointed to state capacity deficits to plan and implement infrastructure projects. This paper aims to investigate the construction of policy instruments for the political state’s capacity to implement large hydroelectric plants in the Brazilian Amazon. We restored to a within-case analysis through the congruence method. Data analysis reveals that despite the development and activation of participatory policy instruments in the Brazilian democratic era, these were not enough to produce high levels of political capacity. Therefore, state bureaucracies still fail in addressing the demands of affected vulnerable groups. This can be explained by the asymmetrical development of political capacity in the structure of public administration; the use of political capacity instruments in the advanced stages of the policy process; the contestation of the mapped demands from the participatory process by state bureaucracies.